Beauty Privilege Perspective Study of Surah Ar-Rum Verse 21 and An-Nisa Verse 1 - Naisha Faradhilla; Arifinsyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The phenomenon of beauty privilege that prioritizes physical appearance as a standard of social acceptance has created gender inequality and psychological pressure, especially for Muslim women in the digital era. Popular culture and social media reinforce visual dominance that places physical beauty above spiritual and intellectual values. In this context, there is a need to review the meaning of beauty in Islam and how the values ​​of piety can be used as a counter-narrative to modern beauty ideology. This study aims to review the concept of privileged beauty from the perspective of the Qur'an using the maudhū'i interpretation approach and critical discourse analysis model of Norman Fairclough. The main data sources consist of verses of QS. Al-Hujurat: 13, QS. An-Nisa: 1, and QS. Ar-Rum: 21–22, accompanied by hadith and interpretations from classical scholars (Ath-Ṭabarī, Ibnu Kathīr) and contemporary (Quraish Shihab, Buya Hamka). This study also involves modern Islamic and sociological literature to understand the socio-cultural dynamics of beauty and identity of Muslim women. The results of the study indicate that piety in the Qur'an is a form of spiritual privilege that is superior to physical beauty. The concepts of qanitat and ḥāfiẓāt lil-ghayb underline the character of faithful women who maintain their honor, obey Allah, and are active in social life. Piety becomes a form of resistance to beauty capitalism and a tool for liberating women's identity from visual pressure. Qur'anic values ​​offer relevant educational and advocacy strategies in building an authentic and empowered Muslim identity in the digital era. This study contributes to the discourse of gender and Islam, by emphasizing that piety is the ultimate beauty privilege in the Islamic paradigm.